Drag reduction of turbulent flow with micro bubbles in vertical pipes - Hisato MINAGAWA; Kazumasa SAKAI; Ryo KURIMOTO; Takahiro YASUDA (Nihon Kikai Gakkai ronbunshu, 2014)
Frictional pressure drop of turbulent upward flow with micro bubbles in a vertical pipe was investigated. To investigate relation between pipe diameter and the frictional pressure drop, three different pipes whose diameters are 5.9, 13 and 16 mm were used. Range of the Reynolds number is from 11000 to 48000. Two kinds of micro bubble generation methods which are pressurized dissolution and shearing methods were used to investigate the frictional pressure drop for a wide range of void fraction α. The conclusions obtained are as follows: (1) the frictional pressure drop of the turbulent upward flows in the vertical pipes increases or decreases by the presence of the micro bubbles, (2) the micro bubble generation method does not affect the drag reduction ratio DR, (3) DR takes a high value at low JL and Re and mainly decreases with increasing JL and Re, (4) DR depends on the pipe diameter, D, at the fixed JL and α, (5) DR depends on D at the fixed Re and α, and increases with D at the fixed Re and α for low α (≤ 0.13%), (6) DR tends to take a positive value for low α (≤ 0.15%), and increases with decreasing α in this condition, (7) the drag increase or reduction of the turbulent upward flow with the micro bubbles in the vertical pipe does not agree with a transition diagram of frictional drag reduction proposed by Murai (2014), (8) the drag is reduced for 0 < α < 0.15% and 11000 < Re < 45000, and mainly is increased for the rest region.